The Effects of orthodontic forces during canine retraction using self-ligating brackets on Gingival Crevicular Fluid Enzyme Activity, Canine Movement and Root Resorption - Rohaya Megat Abdul Wahab,; Zulham Yamamoto,; Albira Sintian,; Nurfathiha Abu Kasim,; Intan Zarina Zainol Abidin,; Sahidan Senafi,; Zaidah Zainal Ariffin,; Shahrul Hisham Zainal Ariffin, (Universiti Kebangsaan Malaysia, 2015)
Alkaline phosphatase (ALP), tartrate-resistant acid phosphatase (TRAP) and aspartate aminotransferase (AST) activities were studied as biomarkers of canine movement. Root resorption was also evaluated in canines subjected to the orthodontic forces. Nineteen subjects randomly received 100 and 150 g force using self-ligating brackets (SLB) either on the right or left site of maxillary arch. Gingival crevicular fluid samples were collected at distal sites of canines for five consecutive weeks. The activities of ALP, TRAP and AST were assayed and measured spectrophotometrically. Canine movement was measured for five consecutive weeks while root resorption was monitored at baseline, week 0 and week 5 using periapical radiographs. In 100 g group, TRAP activity significantly increased in week 3-5 when compared to TRAP baseline activity. However, ALP and AST activities slightly increased. In 150 g group, ALP and TRAP activities slightly increased when compared with their baseline activities. However, AST significantly increased in week 5. Canine movement and root resorption were not significantly different (p<0.05) in both groups. A force of 100 and 150 g slightly increased the bone modeling process and resulted in similar canine movement and root resorption. Therefore, 100 g force could be an optimum force for canine retraction and is preferable (compared with 150 g force) in canine retraction using SLB.